2011
DOI: 10.1177/0300985811400447
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific Diagnostic Marker for Transmissible Facial Tumors of Tasmanian Devils

Abstract: Devil facial tumor disease (DFTD) is a transmissible neoplasm that is threatening the survival of the Tasmanian devil. Genetic analyses have indicated that the disease is a peripheral nerve sheath neoplasm of Schwann cell origin. DFTD cells express genes characteristic of myelinating Schwann cells, and periaxin, a Schwann cell protein, has been proposed as a marker for the disease. Diagnosis of DFTD is currently based on histopathology, cytogenetics, and clinical appearance of the disease in affected animals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 39 publications
3
56
0
Order By: Relevance
“…Murchison and colleagues found that certain Schwann-cell markers are expressed across all tumors, but clearly other markers are variably expressed: NGFR (65%), nestin (45%), neuron-specific enolase (15%), and myelin basic protein by only 10% of tumors. Such patterns are evident for both primary and metastatic disease [2,9]. Similar, although less pronounced, observations can be made from an earlier study where 28% of DFTD cases expressed mel A [8].…”
Section: Evidence For Heterogeneity Of Cell Lineage Specification In supporting
confidence: 84%
See 2 more Smart Citations
“…Murchison and colleagues found that certain Schwann-cell markers are expressed across all tumors, but clearly other markers are variably expressed: NGFR (65%), nestin (45%), neuron-specific enolase (15%), and myelin basic protein by only 10% of tumors. Such patterns are evident for both primary and metastatic disease [2,9]. Similar, although less pronounced, observations can be made from an earlier study where 28% of DFTD cases expressed mel A [8].…”
Section: Evidence For Heterogeneity Of Cell Lineage Specification In supporting
confidence: 84%
“…Histologically, DFTD is an undifferentiated cancer, with tumor phenotype and cell of origin being the subjects of several studies. All available immunocytochemical data suggests a neural crest derivation [8], with more recent data supporting a Schwann cell origin [2,9]. If this is the case, then DFTD should be considered a malignant peripheral nerve sheath tumor (MPNST).…”
Section: History and Natural History Of Ctvt And Dftdmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Furthermore, tumors from RV and SN were negative for periaxin (PRX), an immunohistochemical marker that is diagnostic for DFT1 (12,17) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Standard hematoxylin and eosin (H&E) and immunohistochemical staining with a periaxin antibody (HPA001868; Sigma Aldrich) were performed on 3-μm paraffin sections from tumor tissues fixed in 10% neutral buffered formalin as previously described (17).…”
Section: Methodsmentioning
confidence: 99%